1975
DOI: 10.1029/rg013i005p00637
|View full text |Cite
|
Sign up to set email alerts
|

Global ozone balance in the natural stratosphere

Abstract: The method of instantaneous rates is a three‐dimensional model that takes the observed distribution of atmospheric species and temperature as input data. The distribution of radiation over wavelength, photochemical rate constants, and reaction rates are evaluated in each cell of the three‐dimensional grid. For certain problems of restricted scope, definite answers can be given by this approach. For example, it is shown that the Chapman reactions and air motions are insufficient to give a global ozone balance; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 45 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…Second, a rise in the tropopause (Santer et al, 2003), due to the warming troposphere, could lead to a decrease in ozone at mid-latitudes (Steinbrecht et al, 1998;Varotsos et al, 2004), but the tropopause rise is also affected by the ozone loss itself (Son et al, 2009), rendering its attribution difficult. Third, here we hypothesise a so-far-notdiscussed mechanism: an acceleration of the lower stratosphere BDC shallow branch (Randel and Wu, 2007;Oman et al, 2010) might increase transport of ozone-poor air to the mid-latitudes from the tropical lower stratosphere (Johnston, 1975;Perliski et al, 1989). The quality of the applied dynamical fields in the specified dynamics models considered in this study, or the way models handle transport in the lower stratosphere (SPARC, 2010;Dietmüller et al, 2017), may be dynamically related reasons why models do not reproduce the observed lower stratospheric ozone changes.…”
Section: Discussionmentioning
confidence: 81%
“…Second, a rise in the tropopause (Santer et al, 2003), due to the warming troposphere, could lead to a decrease in ozone at mid-latitudes (Steinbrecht et al, 1998;Varotsos et al, 2004), but the tropopause rise is also affected by the ozone loss itself (Son et al, 2009), rendering its attribution difficult. Third, here we hypothesise a so-far-notdiscussed mechanism: an acceleration of the lower stratosphere BDC shallow branch (Randel and Wu, 2007;Oman et al, 2010) might increase transport of ozone-poor air to the mid-latitudes from the tropical lower stratosphere (Johnston, 1975;Perliski et al, 1989). The quality of the applied dynamical fields in the specified dynamics models considered in this study, or the way models handle transport in the lower stratosphere (SPARC, 2010;Dietmüller et al, 2017), may be dynamically related reasons why models do not reproduce the observed lower stratospheric ozone changes.…”
Section: Discussionmentioning
confidence: 81%
“…In the Southern Hemisphere from January to March (Figures 5a–5c) summer ozone loss [e.g., Johnston , 1975; Farman , 1985] is noticeable by a general decline of ozone at altitudes above 20 km (550 K). In the ILAS/ILAS‐II data a negative correlation is found at all altitude levels (Figures 5a–5c) from January to March.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis of the chemical loss terms for ozone uses the concept of rate‐determining steps as described in Johnston [1975]. As an example the loss rate in molecules/cm 3 /sec for pure oxygen reactions is LossOx=kO,O3TOO3 where k O,O3 (T) is the temperature‐dependent reaction rate coefficient for the reaction of O atoms with O 3 molecules given by k O,O3 (T) = 8.0 × 10 −12 e (−2060/T) cm 3 /molecule/sec [ Sander et al , 2011], [O] is the number density of oxygen atoms, and [O 3 ] is the number density of ozone molecules.…”
Section: Chemistry Climate Model: What Do We Expect For Ozone‐temperamentioning
confidence: 99%